The role of urban living labs in entrepreneurship, energy, and governance of smart cities - Pego, Ana (2019)
Urban living labs (ULL) are a new concept which involves users in innovation and development and are regarded as a way of meeting the innovation challenges faced by information and communication technology (ICT) service providers. The chapter focuses on the role of urban living labs in entrepreneurship, energy and governance of smart cities, where it is performed the relationship between innovations, governance, and renewable energy. The methodology proposed will focus on content analysis and on the exploration of some European examples of implemented ULL, namely Amsterdam, Helsinki, Stockholm and Copenhagen. The contributions of the present research should be the consolidation of knowledge about the impact of ULL on innovation and development of smart cities regarding the concepts of renewable energy, smart governance and entrepreneurship.